Keberadaan Avivauna Sebagai Dampak Pembangunan Taman Keanekaragaman Hayati (KEHATI) Pt. Tirta Investama Pabrik Solok - Gusmardi Indra; Firman Hidayat; Eko Subrata; Fauzan Fauzan; Heriyanto Heriyanto; First San Hendra Rivai (LPPM Universitas Muhammadiyah Sumatera Barat, 2023)
ABSTRACTIndonesia is one of the world's megabiodiversity countries, but it is also a country with a high reduction in biodiversity, so efforts need to be made to maintain this biodiversity. One of these efforts is to build a Taman Keanekaragaman Hayati, as has been done by PT. Tirta InvestamaPabrikSolok. The existence of a biodiversity park will certainly attract animals, especially birds, to come. In order to determine the extent of the presence of these birds, a study was carried out with the aim of obtaining data on bird species, the level of diversity, abundance and diversity as well as their conservation status. The research was conducted from June to July 2023 using the point count method. Placed as many as 6 counting points in an area of 2.5 ha. The results of the study found 31 species belonging to 16 families, with the Nectarinidae and Pycnonotidae families having the highest number of species. The bird diversity index was 2.7130 (medium), the evenness index was 0.7900 (high) and the dominance index was 0.0896 (low). Insectivorous birds were found at 58%, granivorous birds 19%, nectivorous 13% and piscivorous birds as much as 10%. 90% are land birds and 10% water birds. One species (3%) was found to be protected nationally, while internationally 3% met VU criteria, 3% NT criteria and 94% LC.